Effect of supplementing crop substrate with defatted pistachio meal on Agaricus bisporus and Pleurotus ostreatus production - Pardo-Giménez, Arturo; Catalán, Luis; Carrasco, Jaime; Álvarez-Ortí, Manuel; Zied, Diego; Pardo, José (Wiley, 2016)
BACKGROUND: This work assesses the agronomic performance of defatted pistachio meal, after oil extraction, as a nutritional substrate supplement when growing the mushroom species Agaricus bisporus (Lange) Imbach and Pleurotus ostreatus (Jacq.) P. Kumm. Materials were applied at different doses at spawning. Along with non-supplemented substrates, commercial nutritional supplements were used as controls. Proximate analysis of mushrooms is also considered. RESULTS: For the cultivation of champignon, defatted pistachio meal has provided larger mushrooms (unitary weight and cap diameter) with firmer texture and greater content in dry weight and protein, without significant alterations in quantitative parameters. For Pleurotus ostreatus, the supplement led to significant yield increase, even providing up to 34.4% of increment compared to non-supplementation with meal, reaching a biological efficiency of 129.9 kg dt(-1) , when applied to the 15 g kg(-1) compost dose. Supplementation has also been conducted to increase dry weight, protein and fibre within carpophores and to decrease the energy value. Defatted pistachio meal has similar or better results compared to the commercial supplements used as reference. CONCLUSIONS: Compost supplementation with defatted pistachio meal in A. bisporus concerns mainly the quantitative parameters (size, texture, dry weight and protein). Based on the results obtained, this technique has greater potential of development for P. ostreatus commercial crops, basically due to expected increases in production, with a direct impact on benefits and crop profitability. © 2015 Society of Chemical Industry.
Keywords: defatted pistachio meal; edible mushrooms; proximate analysis; quality; substrate supplement; yield